Sound systems design and optimization : modern techniques and tools for sound system design and alignment - McCarthy, Bob (Focal Press, 2010)
In this guide to sound reinforcement alignment and design, Bob McCarthy shares his expert knowledge and effective methodology from years of teaching audio professionals. Written in a clear and easy-to-read style and illustrated with color diagrams and screenshots throughout, McCarthy's unique guide gives you all the newest techniques to ensure perfect sound reinforcement and fulfill design needs. Outlining how sound is spread over a listening area, looking at the physics of speaker interaction, methods of alignment including mic placement, equalization, speaker placement and acoustic treatment, and now including case studies offering real world examples to fully explore different principals discussed, this book provides the definitive guide to sound reinforcement design and optimization.